EFL Teachers' and Students' Perceptions of Using Google Jamboard as Creative Media in English Classroom - Alfi Nur Diniyah; Hertiki (Indonesia Technology-Enhanced Language Learning (iTELL) Journal, 2024)
Creativity is any activity that brings the results that are innovative, useful, and easy to understand. In classroom, the teacher needs an application to support the teaching and learning process. Google Jamboard is a digital whiteboard that has been integrated with various cloud services to facilitate collaboration between teachers and students to make learning more interesting and interactive in the classroom. Google Jamboard application is an alternative for English teachers in teaching materials that require detail and help students explore their ideas. More specifically, this research discusses teachers and student perceptions of Google Jamboard as a creative medium in English classroom. The research method is qualitative and used a case study design. Participants were teachers and students of grade eleventh in SMA Negeri 4 Sidaorjo. The data in this research were obtained from interviews as primary data, and observation as supporting data. The results from teachers’ perceptions were Google Jamboard is interactive media for collaborative learning in teaching English, Google Jamboard helps teachers to be more creative in English classroom, and Google Jamboard supports teachers to present material in English class. The results of students’ perceptions were Google Jamboard supports student creativity in the classroom, The students understand the material easily using Google Jamboard, Google Jamboard supports teacher-students interaction when learning in classroom. Based on the results, it can be concluded that Google Jamboard is the appropriate medium for teachers and students to be more creative in English classroom.